Perancangan Prototipe Media Konsultasi Berbasis Artificial Intelegence dalam Meningkatkan Efektifitas Magang Internasional di Sektor Hospitality - Ida Ayu Wintari Dewi; Made Budiarsa; Putu Herny Susanti (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The research entitled "Designing an Artificial Intelligence-Based Consultation Media Prototype to Increase the Effectiveness of International Internships in the Hospitality Sector" aims to produce a consultation media prototype that utilizes artificial intelligence technology as a means of mentoring for internship candidates. This research uses a descriptive qualitative method with a case study approach at PT. Ama Kodya, where data is obtained through observations of 200 prospective participants, interviews with two expert sources representing the fields of information technology and graphic design, and documentation. In its design, the research combines Natural Language Processing (NLP) theory to develop the ability of artificial intelligence to understand and respond to human language, with User Experience (UX) theory that focuses on designing user interfaces to be easier, more comfortable, and more interactive. The results show that an NLP-based chatbot is the most suitable form of AI to meet the needs of this consultation media, because the chatbot is able to convey information, directions, and guidance in an interactive, contextual manner, and adapts its communication style to the user’s condition. The chatbot can only be accessed through the official website of PT. Ama Kodya so that its security is guaranteed and can be controlled according to company standards. The research findings also formulated a systematic design model that can be used as a guideline in developing similar digital consultation media in the future. Based on the study results, it was concluded that an AI-based chatbot with an NLP and UX approach was proven to be able to improve participant readiness in participating in international internship programs, provide a personalized and adaptive consultation experience, and can support the creation of an effective, efficient, and user-friendly consultation service program, thereby strengthening the quality of internship programs in the hospitality sector as a whole.